Exergoeconomic optimisation of an aqua-ammonia absorption refrigeration system. (15th November 2004) - Sahoo, P.K.; Misra, R.D.; Gupta, A.
Optimisation of thermal systems is generally based on thermodynamic analysis. However, the systems so optimised are often not viable due to economic constraints. In this paper, an attempt is made to minimise the overall operation and amortisation cost of an aqua-ammonia vapour absorption refrigeration system for air-conditioning application using the theory of exergetic cost. This simplified optimisation technique shows significant reduction in product cost (14.50%) with a small increment in investment cost (1.81%).